HIGH SCHOOL STUDENTS’ READING HABIT AND PERCEPTION ON READING FOR PLEASURE - Maharsi, Ista; Ghali, Muhammad Izam; Maulani, Salma (International Journal of Indonesian Education and Teaching (IJIET), 2019)
This paper aims to identify high school students’ reading habit and describe their perceptions on reading for pleasure. There were 41 high school students grade XI involved in this study. Data were collected from questionnaires, observation, and an interview. Results indicate that during holidays nearly 50% of the students read sometimes, 12% read once a week, 9% once in a month, and 29% never read although books are available. The students agree that reading for pleasure give many benefits, but the quantitative data indicate students’ low interest in reading. This may be due to the reading culture which has not been sufficiently developed since the early ages. In addition, the availability and accessibility of reading materials seems to play roles in determining the students’ reading interest. Reading materials should also vary in genres, in themes, and in forms of both printed and on-screen regarding students’ digital nativity. This study has, therefore, initiated the needs for libraries with good book collection, facilities, and interesting design to attract students.DOI: doi.org/10.24071/ijiet.2019.030108